Steel desulfurization on RH degasser: physical and mathematical modeling - Silva,Antonio Marlon Barros (2022)
Abstract Due to the high-quality steel demand, especially for ultra-low Sulfur steel, RH desulfurization has been practiced. Based on this, mathematical and physical modeling have been applied to study steel desulfurization by reagent addition in the RH degasser vacuum chamber. The main result of cold modeling, using water and oil emulating steel and slag, respectively, was to assess the influence of density difference between the continuous and disperse phases on oil droplet behavior. It is shown that its flow tends to be more restricted near the down snorkel when the density difference increases. Moreover, these results provide the basis for CFD modeling validation, which enabled the determination of slag drop residence time inside steel on RH and the average value of the rate of dissipation of turbulent kinetic energy inside the RH ladle. These two parameters were used to develop a kinetic model, which reaches a good agreement with industrial trial results available in literature. The optimum desulfurization degree of 31.44% was achieved for a gas flow rate of 90 Nm3/h, according to the kinetic model. This value can be useful in some steel grade production, where the required S content is less than 10 ppm. Even in common steel grade production, if some punctual chemical adjustment is necessary, this technique is also useful. The main kinetic parameter for steel desulfurization is the steel circulation rate. For best results, it should be reduced in the desulfurization stage, and after that, the normal operation can be resumed, so that the production cycle is not affected.